Glutamine’s double-edged sword: fueling tumor growth and offering therapeutic hope - Fang, Liguang; Gao, Dandan; Jiang, Zuomin; Li, Guoliang; Li, Ming (Frontiers in Immunology, 2025)
Tumor metabolic reprogramming is a highly complex process that enables tumor survival in the presence of limited nutrients, involving multiple signaling pathways, non-coding RNAs (ncRNAs), and transcription factors. Lately, glutamine has been found to enhance the growth, spread, and drug resistance of cancer cells, while also fostering an immunosuppressive microenvironment that aids tumor development. However, in some tumors, such as pancreatic cancer and melanoma, additional glutamine can inhibit the proliferation of tumor cells, and this mechanism is closely related to the regulation of the immune microenvironment. Therefore, further exploration of glutamine metabolism in tumors is essential for understanding the pathogenesis of cancer and for developing new metabolically targeted therapies. We systematically review the latest research on the reprogramming of glutamine metabolism and its role of tumor growth, spread, and immune system regulation. Additionally, we review the clinical research progress on targeted glutamine therapies and their application in combination with current anti-tumor treatments. Ultimately, we address the challenges and prospects involved in resistance to anti-cancer strategies aimed at glutamine metabolism.